Settlement Of Industrial Relations Disputes Due To Termination Of Employment Due To Efficiency In Maintaining Balance Between Employers And Workers - Sudirgo, Tony; Iryani, Dewi; Setiawan, Puguh Aji Hari (Ilmu Hukum Prima (IHP), 2025)
Regulations related to termination of employment for reasons of efficiency are not explained explicitly, this will have an impact on the emergence of industrial relations disputes, thus affecting the balance between the interests of employers and the protection of workers/laborers. This study aims to examine the regulations regarding termination of employment for reasons of efficiency based on laws and judges' decisions and efforts to resolve them to ensure justice for the parties. In this study, a normative juridical method is used with a statutory and case approach, where this study analyzes Law Number 13 of 2003, Law Number 6 of 2023, Government Regulation Number 35 of 2021, and decisions such as the Constitutional Court Number 19/PUU-IX/2011. With the findings of ambiguity in the definition of efficiency, the phrase loss, and prevention of potential losses, which are seen in the cases of PT. S against Mrs. E and PT. Jtrust Olympindo Multi Finance against Sudadi Hari Widianto, causing misuse of efficiency reasons in termination of employment. Thus, in its implications, it is necessary to update regulations with a more explicit definition of efficiency, strengthening the role of judges in analyzing company financial audit reports, and transparent steps by companies such as analyzing the company's macro and micro conditions in advance and mapping workers/laborers to ensure the achievement of justice, benefits, and legal certainty, so as to support a harmonious balance in industrial relations.